Detecting jellyfish sign in a patient with systemic lupus erythematosus: An added value of the echocardiography - Menaisy, Marha M. (Indian Journal of Case Reports, 2021)
Systemic lupus erythematosus (SLE) is an autoimmune disease that affects nearly every organ of the body. Cardiopulmonary manifestations are common in SLE, almost in the form of serositis, and include pleural and pericardial effusions. In these patients, echocardiography is an excellent non-invasive tool for detecting pericardial effusion and may provide a hint about pleural effusion. We report the case of a 20-year-old woman with SLE who had been experiencing dyspnea for 1 month and had no prior history of cardiovascular or pulmonary disease. A rheumatologist referred her to our echocardiography lab for a cardiac evaluation. In the echocardiographic examination, pleural mass depended from the left visceral pleura was discovered, surrounded by massive pleural effusion that induced left lung atelectasis (Jellyfish sign, and complete atelectasis of a lung lobe floats above a massive pleural effusion).